ANALISIS NERACA PERDAGANGAN PETERNAKAN DAN SWASEMBADA DAGING SAPI 2014 - Budiyono, Haris (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
The balance of trade (or net exports, sometimes symbolized as NX) is the difference between the monetary value of exports and imports of output in an economy over a certain period. It is the relationship between a nation's imports and exports. The balance of trade in agricultural sector for the period 2005-2009 should be analyzed and described to understand what challenges should be managed to achieve a better figure of agriculture development in Indonesia, particularly in livestock industri in the next 5 years period, 2010-2014. Meanwhile, it has been rescheduled that Indonesia in the year 2014 will move to the state of meat selfsufficiency, after it was missed for twice as a goal in 2005 and 2010. In this paper, the meat self suffiency 2014 also will be analyzed an explained in order to have a clear picture of the possibility achievement toward the goal at 3 (three) scenario, pessimistic, more likely, and optimistic.